Ultrastructural change in lignocellulosic biomass during hydrothermal pretreatment. (December 2021) - Sun, Qian; Chen, Wei-Jing; Pang, Bo; Sun, Zhuohua; Lam, Su Shiung; Sonne, Christian; Yuan, Tong-Qi
Graphical abstract: Highlights: The basic principles and developments of hydrothermal pretreatment are reviewed. The ultrastructural alterations during hydrothermal pretreatment are discussed. The effects of hydrothermal pretreatment on bioethanol production are addressed. The prospects for future developments are proposed and discussed. Abstract: In recent years, visualization and characterization of lignocellulose at different scales elucidate the modifications of its ultrastructural and chemical features during hydrothermal pretreatment which include degradation and dissolving of hemicelluloses, swelling and partial hydrolysis of cellulose, melting and redepositing a part of lignin in the surface. As a result, cell walls are swollen, deformed and de-laminated from the adjacent layer, lead to a range of revealed droplets that appear on and within cell walls. Moreover, the certain extent morphological changes significantly promote the downstream processing steps, especially for enzymatic hydrolysis and anaerobic fermentation to bioethanol by increasing the contact area with enzymes. However, the formation of pseudo-lignin hinders the accessibility of cellulase to cellulose, which decreases the efficiency of enzymatic hydrolysis. This review is intended to bridge the gap between the microstructure studies and value-added applications of lignocellulose while inspiring more research prospects to enhance the hydrothermal pretreatment process.